Dignity of work and full employment - Annamaria Simonazzi (PSL Quarterly Review, 2021)
The paper offers a brief reconstruction of the varying fortunes of the Charter of Workers' Rights, interpreted in light of the evolution of economic thinking on the role of the market - especially of the labor market - and on the reversal that has been made of the role of labor policy in relation to macroeconomic policy. It is argued that much of the problems facing our economies today are due to this reversal of roles. The author concludes that industrial relations and the world of work should enter in the remit of industrial policy due to the importance that the accumulation of individual and collective knowedge within firms have for the innovation of companies and the economic system of a country, as well as for reasons of justice.
Keywords: J5; J23; E24; 330; employment; welfare